Utilization Of Fruits, Leaves, And Petioles Extract Of Bilimbi (Averrrhoa Bilimbi Linn.) In Detergent Synthesis - Muhammad Triyogo Adiwibowo; Dela Ayu Fitria; Karen Erlangga; Wardalia Wardalia (JURNAL INTEGRASI PROSES, 2021)
Bilimbi (Averrhoa bilimbi Linn.) contains saponins which are natural surfactants. Due to their cleaning properties, saponins can be developed as raw materials for detergent production. The synthesis of detergent with the addition of fruits, leaves, and petioles extract of the bilimbi has been successfully carried out. A series of tests, namely organoleptic, pH, foam stability and quantity, hedonic, and detergency tests, were performed to evaluate the quality of detergents. From the organoleptic test, it was found that the addition of the extract caused the detergent to change color to brownish, with a slight increase in density and a slight decrease in pH, and relatively did not change the phase and fragrance of the detergent. The addition of extract did not increase the quantity of foam produced but could increase the stability of the resulting foam. The hedonic test shows a relatively good level of panelist preference. The detergency from the stain removal test shows that the detergent has fairly good detergency.